2012
DOI: 10.5114/bta.2012.46577
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH PAPER Identification and characterization of genes connected with flower morphogenesis in cucumber

Abstract: Sex determination and flower morphogenesis are very broad and complex processes controlled at many levels. Four clones have been isolated from cucumber transcriptomes, mapped onto the cucumber genome and checked if the corresponding genes expression differed between the vegetative and generative tissues (leaf, shoot apex, and 1-to 2-mm flower buds) of monoecious and gynoecious cucumber lines. To determine the role, and characteristics of identified genes in flower morphogenesis, as well as to understand the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Genome sequencing and structural and functional annotation of its sequence provide us with a large dataset, among which are some potentially important genes for crop improvement. For example in 2009 Li et al study, using the genome sequence, authors were able to successfully clone and identify the M/m gene involved in sex determination in cucumber [30] and the GY/gy involved in sex determination was connected with CsPSTK1-kinase [31]. The other genes and markers of great breeding importance, thanks to mapping population and the whole genome sequence of cucumber was also discovered.…”
Section: The Utility Of Ngs In Mapping Technologymentioning
confidence: 92%
“…Genome sequencing and structural and functional annotation of its sequence provide us with a large dataset, among which are some potentially important genes for crop improvement. For example in 2009 Li et al study, using the genome sequence, authors were able to successfully clone and identify the M/m gene involved in sex determination in cucumber [30] and the GY/gy involved in sex determination was connected with CsPSTK1-kinase [31]. The other genes and markers of great breeding importance, thanks to mapping population and the whole genome sequence of cucumber was also discovered.…”
Section: The Utility Of Ngs In Mapping Technologymentioning
confidence: 92%
“…gy (gynoecious)-This recessive allele is responsible for femininity that is much more highly stable than that conferred by the F gene (recessive femininity rF; Bhard femininity^). The gy gene (also abbreviated as g) is frequently assumed to be the gene indirectly influencing sex (Pawełkowicz et al 2012) and it could be correlated with CsWIP (Boualem et al 2015). h (andromonoecious-2)-This allele produces bisexual flowers with normal ovaries (Kubicki 1974).…”
Section: Genetic Factors Controlling Sex Determination In Cucumbermentioning
confidence: 99%
“…Whereas information on the function of the F and M genes is described, little is known about the functions of A/a, Gy/gy, and H/h alleles. In one study, the A/a allele was suggested to be linked to the copper transporter gene CsRAN1 (Terefe 2005), whereas the dominant allele Gy/gy gene can be correlated with the putative serine/threonine kinase gene CsPSTK1 (Pawełkowicz et al 2012). Because CsPSTK1 expression is related to the recessive gy allele, the associated inhibition of the CsPSTK1 gene may require the presence of the dominant Gy allele.…”
Section: Genetic Factors Controlling Sex Determination In Cucumbermentioning
confidence: 99%
See 2 more Smart Citations